The Spread and Changes of Tea and Tea Drinking Customs in Minority Areas of North and the Tibetan Plateau in China - Liu, Zhiyang (International journal of business anthropology, 2024)
There is currently no consensus on when Chinese people began to drink tea. The way people drank tea before the Tang Dynasty was controversial in the tea academic community due to insufficient historical materials. Since the Tang Dynasty, tea drinking became popular in the hinterland. Due to climate and soil condition restrictions, acidic soil areas south of the Qinling Mountains and the Huai River were main tea producing area. Therefore, the ethnic groups in northern frontier areas must obtain tea through trading with inland tea areas. Therefore, tea was introduced into northern minority areas and the Tibetan Plateau relatively late. It was not until the Song Dynasty that there were precise records on tea drinking by northern ethnic minorities, and tea-horse trade became an important form of material exchange between agricultural and nomadic peoples at that time. In addition to well-known tea-horse trade between Song and northwest Tibet, Liao, Jin and other northern kingdoms also exchanged tea with the Song Empire in frontier trade. Tea-horse trade became an important material exchange channel between the Central Plains and nomadic peoples at that time. In the Yuan Dynasty, the Mongols dominated the Central Plains, and coexisted with Han and other ethnic groups, inevitably leading to cultural and customs exchanges and integration. One of the manifestations is that the Mongols who went south of the Great Wall began to drink tea generally and integrated the tea drinking method and customs of the Han people in the Central Plains with their own lifestyle. They added dairies favored by nomadic peoples to tea and gave rise to butter tea or milk tea. After the establishment of the Ming Dynasty, the inland Han people no longer drank butter tea, while the Mongols who retreated north of the Great Wall maintained their tea drinking customs.